ER stress and unfolded protein response in ocular health and disease. (20th June 2018) - Kroeger, Heike; Chiang, Wei‐Chieh; Felden, Julia; Nguyen, Amanda; Lin, Jonathan H.
Abstract : The human eye is the organ that is able to react to light in order to provide sharp three‐dimensional and colored images. Unfortunately, the health of the eye can be impacted by various stimuli that can lead to vision loss, such as environmental changes, genetic mutations, or aging. Endoplasmic reticulum (ER) stress and unfolded protein response (UPR) signaling have been detected in many diverse ocular diseases, and chemical and genetic approaches to modulate ER stress and specific UPR regulatory molecules have shown beneficial effects in animal models of eye disease. This review highlights specific eye diseases associated with ER stress and UPR activity, based on a recent symposia exploring this theme. Abstract : The Human eye is a vulnerable organ in the body. Many factors can impact the health of the human eye leading to changes in the quality of our vision. The presence of Endoplasmic reticulum stress and the induction of the Unfolded Protein Response are hallmarks of many retinal diseases; and may be potential mechanisms for therapeutic intervention.